Peran Bahasa Tubuh Dalam Membangun Kepercayaan Pada Interaksi Pertama ( Studi Etnometodologi Pada Remaja Kota Bandung) - Almadina Rakhmaniar (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2023)
This study aims to examine the role of body language in building trust in first interactions among teenagers in Bandung City. Through an ethnomethodological approach, this study analyzes various nonverbal elements such as facial expressions, hand gestures, body posture, and proxemics that influence perceptions of trust. Data was collected through participatory observation, in-depth interviews, and video analysis. The results show that body language plays a crucial role in establishing trust at the first interaction. A genuine smile and consistent eye contact are key indicators used by adolescents to assess trust. Open hand gestures and upright posture also contribute positively to perceptions of trust.Appropriate interpersonal distance helps create a sense of comfort and trust, while a warm tone of voice and a moderate pace of speech increase perceptions of sincerity. Local cultural norms and the influence of global trends affect the way adolescents use body language in their interactions. Gender differences were also found, with adolescent girls being more expressive in hand gestures and facial expressions, while adolescent boys relied more on body posture and tone of voice. The study concludes that understanding and effective use of body language is key in building trust in first interactions. Practical implications of the findings include developing nonverbal communication skills in adolescent education and increasing cultural awareness in social interactions.